Photocatalytic H2 production on self-decorated Au nanoparticles/TiO2 nanotubes under visible light - Lee, Kiyoung; Hahn, Robert; Schmuki, Patrik (Electrochemistry Communications, 2014)
In the present work we fabricate TiO2 nanotubes that are self-decorated with Au nanoparticles by anodizing low concentration (0.02 and 0.2 at.% Au) TiAu alloys. After formation, the TiO2 tube walls carry regularly dispersed self-decorated Au particles with 5 nm in diameter which cause significant surface plasmon resonances. This plasmon resonance effect can be exploited to achieve visible photoresponse and can be used for photocatalytic H2 production under visible light illumination.
EAM Import::2019-03-12